ANALISIS MOTIVASI PASIEN BPJS DAN PASIEN UMUM TERHADAP PELAYANAN DI KLINIK JEPUN KURIPAN KABUPATEN LOMBOK BARAT TAHUN 2024 - Putri Amelia Silvi; Syatriawan Perdana Putra (Nusadaya Journal of Multidiciplinary Studies, 2024)
The aim of this research is to analyze the motivation of BPJS patients and general patients towards services at the Jepun Kuripan Clinic in West Lombok in 2024. And the specific aim of this research is to describe the motivation of BPJS patients and general patients at the Jepun Kuripan Clinic in West Lombok in 2024, to describe the quality of service received by BPJS patients and general patients at Jepun Kuripan Clinic, West Lombok in 2024. Analyzing the relationship between Motivation and Service Quality received by BPJS patients and general patients at Jepun Kuripan Clinic, West Lombok in 2024. The research design that will be used in this study is an analytical observational research design with a cross-sectional approach. The population of this study were all patients who sought treatment and received health services, both BPJS patients and general patients at the Jepun Kuripan Clinic, West Lombok. The number of samples in this study was "quota sampling" of 100 respondents, and the sample was taken by accidental sampling. The data collection techniques used in this research were interviews and questionnaires. The data analysis technique in this research is the Univariate Test and Bivariate Test using the Kendall'tau-b Test. The results of this research analysis after carrying out the Kendall tau -b test, the value with a correlation coefficient of 0.469 shows that the direction of the correlation is positive. This means that the higher the patient's motivation, the higher the quality of service felt by the patient. The strength of the relationship between patient motivation and service quality has "medium" strength, and vice versa between service quality and patient motivation.